Partai Golongan Karya Digoyang Konflik Internal Berimbas Ke Kalimantan Timur - Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
The aim of this research is to know the internal conflict in GOLKAR partai which HAS influenced to the local governments. The method of the research is library one. The references are taken from the literature of the library in Universitas 17 Agustus 1945 Samarinda. The most signicant materials are taken from the local newspaper Tribun Kaltim and Kaltimpost. The research has been carried out for one month in Samarinda. Polical party is the key of the governmet so it is badly needed to support the legislative, executive and judicative as well because it is the representative body of the peoples. So if it is involved the conflict either the internal or external it will disturb not only the government but also the state. Really any conflict will make emotion and anger which are dangerous for the peoples throughout the country. The conflict started from the error of some members to hold a National Dialog in Bali which must be held in January 2015 not in December 2014 as arranged in the decision of the Riau National Dialog. Then it has become the fire of he conflict between the two blocks  of Aburzal Bakrie against Agung Laksono. The main core of conflict is egoism. It causes to make two blocks which are useless. The results of the conflict is the loss of the peoples’trust. The two blocks directed by Vice President Yusup Kala and the president Joko Widodo will help them solve the problems. The suggestions of this research is (1).Both have a good will (2).Both must arrange the National Dialog (3).No one will be dominant (4).If the conflict goes on it will be collapsed.